The Dispute Settlement through International Arbitration between PT. Karaha Bodas Company against PT. Pertamina and PLN - Rahma Yunita Soviani; Ery Agus Priyono (Jurnal Daulat Hukum, 2022)
Arbitration is a dispute resolution institution that uses an adversarial approach with the result that win lose chosen as an alternative by business people. Alternative dispute resolution that is currently in demand is through arbitration because it is in line with the increase in commercial transactions in the business sector both nationally and internationally. Dispute resolution through arbitration provides benefits for the disputing parties. These advantages include the confidentiality of the disputing parties, relatively cheaper costs, a fast, efficient dispute resolution process and provide flexibility for the disputing parties. International arbitration dispute resolution has a uniqueness which adheres to the principle of final and binding (last resort and binding). An international arbitral award that has been decided abroad if it is brought to Indonesia, there are two possibilities, i.e. the International arbitral award asks to be enforced or annulled. Based on the dispute between PT. Pertamina against Karaha Bodas Company that Pertamina cannot cancel the arbitration award that has been handed down by the Swiss Arbitration Board. The reasons for rejection and cancellation are as stated in the New York Convention and the UNCITRAL Model Law.